Interval Iterative Methods Under Partial Ordering（Ⅰ） (Journal of Computational Mathematics, 2018)
Many types of nonlinear systems, which can be solved by ordered iterative methods, are discussed in unified form in the present paper. Under different initial conditions, some generalized ordered iterative methods are given, and the existence and uniqueness of the solution and the convergence of the methods are proved.